Расщепление 2-гидразинобензо[h]хиназолинов - А. И. Маркосян (ՀՀ ԳԱԱ հրատ.)
Հայտնաբերվել է, որ 3-տեղակալված 2-հիդրազինա-4-օքսո-3,4,5,6-տետրահիդրոսպիրո(բենզո[h]խինազոլին-5,1΄-ցիկլոհեքսանները) էթանոլային լուծույթում հիմքի ներկայությամբ ենթարկվում են ճեղքման՝ առաջացնելով 2-րդ դիրքում չտեղակալված տետրահիդրոսպիրո(բենզո[h]խինազոլին-5,1΄-ցիկլոհեքսաններ): It is revealed that 3-substituted 2-hydrazino-4-oxo-3,4,5,6-tetrahydro(benzo[h] quinazoline-5,1 '- cyclohexanes) in ethanolic solution in the presence of the base are exposed to splitting that results in non-subtituted tetrahydrospiro(benzo[h]quinazoline- 5,1 '-cyclohexanes) in the second position.
Keywords: Chemistry